2015
DOI: 10.4172/2368-0512.1000031
|View full text |Cite
|
Sign up to set email alerts
|

The effects of glycine, glutamate and their combination on cardiodynamics, coronary flow and oxidative stress in isolated rat hearts

Abstract: ObJeCTIVeS: To examine the effects of glycine, glutamate and their combination on cardiac function, coronary flow and oxidative stress in isolated rat hearts, and to examine the effects of potential activation of N-methyl-Daspartate (NMDA) receptors in isolated rat hearts. MeThODS: The hearts of male Wistar albino rats were excised and perfused according to the Langendorff technique, and cardiodynamic parameters (maximum rate of pressure development in the left ventricle [dp/dt max]; minimum rate of pressure d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
2
2
0
Order By: Relevance
“…Similar to previously published results, SLVP and DLVP did not change during glutamate administration [ 31 ], while the activation of NMDARs by TG induced pressor response. Most studies dealing with the effects of NMDAR and blood pressure are related to the modulation of central NMDARs and consequent pressor response [ 43 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar to previously published results, SLVP and DLVP did not change during glutamate administration [ 31 ], while the activation of NMDARs by TG induced pressor response. Most studies dealing with the effects of NMDAR and blood pressure are related to the modulation of central NMDARs and consequent pressor response [ 43 ].…”
Section: Discussionsupporting
confidence: 91%
“…Some future research on assessing the place of cardiac NMDARs in heart homeostasis should be directed to clarifying their role in the orchestration of different signaling pathways in I/R. Similar to previously published results, SLVP and DLVP did not change during glutamate administration [31], while the activation of NMDARs by TG induced pressor response. Most studies dealing with the effects of NMDAR and blood pressure are related to the modulation of central NMDARs and consequent pressor response [43].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Results of experiments conducted by our research group also indicated the role of NMDA receptors in regulation of heart function. Application of glutamate or glicine did not induce any change in heart function, coronary flow or oxidative stress in retrogradely perfused rat hearts according to Langendorff technique, while on the other hand their combined use caused decrease in observed cardiodynamic parameters, coronary flow and increase in oxidative stress biomarkers (64). In the case of the combined use of glutamate and/or glycine with verapamil (blocker of L type Ca 2+ channels) in the same experimental model, the slightest changes were observed in the group where verapamil was administered along with glutamate and glycine, which suggests that the activation of the NMDA receptors allows the influx of certain amounts of Ca 2+ , insufficient to nullifies the effects of verapamil, but sufficient enough to significantly increase observed cardiodynamic parameters compared to other experimental groups in this study (65).…”
Section: Nmda Receptors and Cardiovascular Systemmentioning
confidence: 79%